'Dust around Nearby Stars' The Survey Observational Results. Issue Volume 8:Issue S299(2013) (6th January 2014) - Marshall, Jonathan P.
Abstract: In this conference proceedings we summarize the key observational findings of the Herschel DUNES survey. We found 31 discs in our sample, equating to an increased dust incidence with Herschel of 20.2 ±2.0% compared to previous measurement of 12.5±5% with Spitzer for the same population of nearby, Sun-like stars. We identify no trend towards fewer discs around later spectral types, as had previously been reported for A-M stars. Around half of the discs exhibit extended emission, representing a vast improvement in the number of spatially resolved debris discs and thereby the quality of modelling that can be applied to those systems. We also identify unusual sub-groups of discs, including 'steep SED' sources with dust spectral indexes in the 70–160 μm range, steeper than the Rayleigh-Jeans tail which, whilst not unheard of, are more typically seen at sub-mm wavelengths and candidate 'cold discs' which are identified through their lack of significant excess emission at wavelengths shorter than 100 μm.